Peripheral Injection of Tim-3 Antibody Attenuates VSV Encephalitis by Enhancing MHC-I Presentation - Li, Ge; Tang, Lili; Hou, Chunmei; Wang, Zhiding; Gao, Yang; Dou, Shuaijie; Mo, Rongliang; Hao, Ying; Gao, Zhenfang; Li, Yuxiang; Dong, Jie; Zhang, Jiyan; et al. (Frontiers in Immunology, 2021)
Viral encephalitis is the most common cause of encephalitis. It is responsible for high morbidity rates, permanent neurological sequelae, and even high mortality rates. The host immune response plays a critical role in preventing or clearing invading pathogens, especially when effective antiviral treatment is lacking. However, due to blockade of the blood-brain barrier, it remains unclear how peripheral immune cells contribute to the fight against intracerebral viruses. Here, we report that peripheral injection of an antibody against human Tim-3, an immune checkpoint inhibitor widely expressed on immune cells, markedly attenuated vesicular stomatitis virus (VSV) encephalitis, marked by decreased mortality and improved neuroethology in mice. Peripheral injection of Tim-3 antibody enhanced the recruitment of immune cells to the brain, increased the expression of major histocompatibility complex-I (MHC-I) on macrophages, and as a result, promoted the activation of VSV-specific CD8+ T cells. Depletion of macrophages abolished the peripheral injection-mediated protection against VSV encephalitis. Notably, for the first time, we found a novel post-translational modification of MHC-I by Tim-3, wherein, by enhancing the expression of MARCH9, Tim-3 promoted the proteasome-dependent degradation of MHC-I via K48-linked ubiquitination in macrophages. These results provide insights into the immune response against intracranial infections; thus, manipulating the peripheral immune cells with Tim-3 antibody to fight viruses in the brain may have potential applications for combating viral encephalitis.